Zika virus phosphoproteome through the computational looking-glass and what we found there? - Basharat, Zarrin; Khan, Tabeer; Yasmin, Azra (PeerJ Preprints, 2016)
Computational phospho-mining and related post translational modification analyses using in silico methods is debateable. For some wet lab scientists, it is similar to the twilight zone, where nothing might be quite what it seems. We certainly agree that the wet lab is critical for validation but computational assays rapidly generate preliminary data for assessment and aid wet lab. Zika virus is wrecking a havoc and it is the need of the hour to rapidly assess various phenomenon associated with its pathogenicity and disseminate it to the scientific community for assessment. Phosphorylation assists in viral replication and its association with host receptors. Here, we present a vignette of the phosphorylation potential of Zika virus proteins.
Keywords: Zika virus; proteome; phosphorylation; Computational biology